Mengelola Inovasi di Sektor Publik Indonesia: Tinjauan Literatur dan Pengembangan Model UTAUT-IPS - Ahmad Bramantyo Nursasotyosidi; Misbahuddin Azzuhri (Journal of Governance Innovation, 2025)
Public sector innovation plays a critical role in addressing global challenges and enhancing the quality of public services. However, in Indonesia, many public sector innovations lack sustainability and fail to be implemented over the long term. This study aims to identify and analyze the factors influencing the sustainability of pulic sector innovation in Indonesia through a literature review approach. By integrating the Unified Theory of Acceptance and Use of Technology for Innovation in the Public Sector (UTAUT-IPS), this review maps relationship between internnal factors (such as managerial support, innovation characteristics, and users’ behavioral intention) and external factors (such as political pressure and cross-sector collaboration) in shaping innovation sustainability. The analysis demonstrates that UTAUT-IPS model offers a comprehensive conceptual framework for understanding and designing strategies to sustain innovation in the public sector. This study contributes theoretically to the development of innovation aadoption and sustainability models, and offers strategic insights for policymakers and public sector practitioners in Indonesia.